The Transformation of Islamic Education - Umar, Muallief; kartikasari, Galuh (EDUTEC : Journal of Education And Technology, 2025)
This study examines the transformation of Islamic education in Indonesia, focusing on the role of pesantren (Islamic boarding schools) in integrating digital literacy and promoting religious moderation. The research was conducted at three pesantren: Pondok Pesantren Miftahul Ula, Pondok Pesantren Annur, and Pondok Pesantren Fajrul Ula. These institutions were chosen for their unique approaches to blending traditional Islamic education with contemporary digital tools. The study uses a qualitative research design, employing interviews, participant observations, and document analysis to collect data from students, educators, and administrators. The analysis focuses on how digital literacy is incorporated into the curricula of these pesantren and how it influences students' understanding of Islamic teachings in the digital era. Additionally, the research investigates the role of these pesantren in fostering a balanced approach to religious practice, promoting tolerance, and encouraging moderation in Islamic thought. The findings suggest that the incorporation of digital technology not only enhances educational accessibility but also contributes to a more inclusive and moderate religious discourse among students. This study concludes that pesantren play a pivotal role in shaping a progressive and harmonious Islamic education system in Indonesia, balancing tradition with modernity.